2017
DOI: 10.1080/00140139.2017.1405081
|View full text |Cite
|
Sign up to set email alerts
|

Exploring organisational competences in Human Factors and UX project work: managing careers, project tactics and organisational strategy

Abstract: Organisational competence in Human Factors and UX (user experience) has not been looked at before despite its relevance to project success. We define organisational competence as the collective competence of the individuals, bringing together their complementary abilities to deliver an outcome that is typically more than the sum of its parts. Twenty-two UX and Human Factors practitioners were interviewed about their project work in two contrasting domains: web design and safety-critical systems to explore orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…One area of opportunity is the inclusion of HFE in User Experience (UX) education. However, there are differences in professional competency requirements with HFE having clearly defined (and established) competencies (IEA and UK) and a lack of 'definitive set of competencies' in UX (Furniss et al, 2018). Possible reasons for the differences are the age of the disciplines (UX is relatively new compared to HFE) and 'the diverse mix of skills and roles that make up the community, making it challenging to identify an agreed set of competencies' (Gray et al, 2015).…”
Section: Course Sustainabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…One area of opportunity is the inclusion of HFE in User Experience (UX) education. However, there are differences in professional competency requirements with HFE having clearly defined (and established) competencies (IEA and UK) and a lack of 'definitive set of competencies' in UX (Furniss et al, 2018). Possible reasons for the differences are the age of the disciplines (UX is relatively new compared to HFE) and 'the diverse mix of skills and roles that make up the community, making it challenging to identify an agreed set of competencies' (Gray et al, 2015).…”
Section: Course Sustainabilitymentioning
confidence: 99%
“…The relative lack of prescription regarding competencies across UX education does not imply less regard for professional competence, rather there is less agreement on what the specific individual competencies are for UX practitioners and how to ensure students are adequately equipped (Hignett & Gyi, 2015). This requires HFE to demonstrate the relevance of its methods and knowledge to achieving desired UX competence, e.g., in areas such as analytic insight (see, Furniss et al, 2018).…”
Section: Course Sustainabilitymentioning
confidence: 99%
“…Project workers can, in the course of a project, generate valuable ideas and knowledge for the organization, who might then have a direct interest in pursuing collaboration with them (Panico, 2009). Many authors have also emphasized the role of discontinuity and uncertainty in project‐based career trajectories (e.g., Lloyd‐Walker et al, 2016) and the crucial importance of adaptability for project workers to build a long‐term career (Furniss et al, 2018).…”
Section: General Backgroundmentioning
confidence: 99%
“…However there are significant differences in competency expectation (and processes) in the disciplines of EHF and User Experience (UX). Furniss et al contrasted professional competency requirements between EHF and UX [11]. They identified that EHF had clearly defined (and established) competencies (IEA and UK) with a lack of 'definitive set of competencies' in UK [12].…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%